Functional Imaging of Evaluation of Diabetic Gastroparesis - Santhanam, Prasanna; Marashdeh, Wael; Solnes, Lilja (Current Diabetes Reviews, 2018)
Introduction: Gastroparesis (a complication of both type 1 and type 2 diabetes mellitus) is delayed gastric emptying in the absence of a mechanical obstruction. Overall prevalence of Gastroparesis is close to 5 % in type 1 diabetes and 1 % in type 2 diabetes. It is unclear if good glycemic control leads to the delay of development and progression of gastroparesis. Methods: Gastric enteric neurons as well as Interstitial Cells of Cajal (ICC) are depleted, truncated and are surrounded by immune infiltrates composed of macrophages. There are associated vagal nerve innervation abnormalities, smooth muscle and Fibroblast Like Cell (FLC) dysfunctions. There is s decrease in HO-1 macrophages and increase in proinflammatory macrophages. Gastric electrical rhythm abnormalities and channelopathies have been implicated in the pathology of gastrointestinal diseases. Results: In patients with diabetes, the most common clinical symptoms include abdominal bloating and pain. Nuclear Medicine Gastric Emptying Scintigraphy (NMGES) is considered the gold standard for evaluation of gastroparesis. Conventional imaging techniques such as fluoroscopic evaluation of gastric emptying can only evaluate the presence or absence of an obstruction. Historically, solid gastric emptying has been the method for evaluation although recent data suggests that liquid gastric emptying may be altered without solid gastric emptying abnormality. It is paramount that a radiotracer for evaluating gastric emptying be tightly bound to ingested food (solid). The most frequent radiotracer used is Tc99msulfur colloid bound to egg whites. In an effort to standardize normal values across institutions, a consensus recommendation published in 2008 called for a 4- hour study utilizing a standardized meal. Conclusion: Nuclear Medicine Gastric Emptying Scintigraphy (NMGES) is the test of choice for evaluation of diabetic gastroparesis. Standard guidelines have been established for the performance and interpretation of the test.
Keywords: fibroblast like cell